Experimental infection of chickens by a flagellated motile strain of Salmonella enterica serovar Gallinarum biovar Gallinarum - Lopes, P.D.; Freitas Neto, O.C.; Batista, D.F.A.; Denadai, J.; Alarcon, M.F.F.; Almeida, A.M.; Vasconcelos, R.O.; Setta, A.; Barrow, P.A.; Berchieri, A. (Elsevier, 2016)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Gallinarum (SG) causes fowl typhoid (FT), a septicaemic disease which can result in high mortality in poultry flocks. The absence of flagella in SG is thought to favour systemic invasion, since bacterial recognition via Toll-like receptor (TLR)-5 does not take place during the early stages of FT. In the present study, chicks susceptible to FT were inoculated with a wild type SG (SG) or its flagellated motile derivative (SG Fla+). In experiment 1, mortality and clinical signs were assessed, whereas in experiment 2, gross pathology, histopathology, systemic invasion and immune responses were evaluated. SG Fla+ infection resulted in later development of clinical signs, lower mortality, lower bacterial numbers in the liver and spleen, and less severe pathological changes compared to SG. The CD8+ T lymphocyte population was higher in the livers of chicks infected with SG at 4 days post-inoculation (dpi). Chicks infected with SG had increased expression of interleukin (IL)-6 mRNA in the caecal tonsil at 1 dpi and increased expression of IL-18 mRNA in the spleen at 4 dpi. In contrast, the CD4+ T lymphocyte population was higher at 6 dpi in the livers of birds infected with SG Fla+. Therefore, flagella appeared to modulate the chicken immune response towards a CD4+ T profile, resulting in more efficient bacterial clearance from systemic sites and milder infection.